Structural Response of Modular Buildings to Multiple Hazards - Lacey, Andrew William (Curtin University, 2020)
This thesis studies the lateral responses of modular steel buildings subjected to wind and earthquake actions. Two new improved inter-module connections are proposed, and experimental, numerical and analytical studies are undertaken to develop simplified models for their structural behaviours. Global numerical simulations are carried out for a case study building incorporating the simplified connections. The simplified models contribute to an improved understanding of the building responses and facilitate the analysis and design of modular structures.